Micronutrient supplementation in pregnancy: Who, what and how much?. (March 2019) - Parisi, F; di Bartolo, I; Savasi, VM; Cetin, I
Pregnancy represents a period of major physiological and metabolic change, aiming to ensure proper fetal growth and development, as well as maternal preservation. This review focuses on maternal nutrition, and particularly on micronutrient deficiencies and supplementation during pregnancy. Nutrient deficiencies and consequences in pregnant women are presented, with an overview of current recommendations for dietary supplementation in pregnancy, even considering the risk of micronutrient overload. Appropriate universal supplementation and prophylaxis/treatment of nutritional needs currently appear to be the most cost-effective goal in low-income countries, thus ensuring adequate intake of key elements including folate, iron, calcium, vitamin D and A. In high-income countries, a proper nutritional assessment and counselling should be mandatory in obstetric care in order to normalize pregestational body mass index, choose a healthy dietary pattern and evaluate the risk of deficiencies.